PERNIKAHAN USIA DINI MENURUT PANDANGAN HUKUM ISLAM - Halim Setiawan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
Marriage is a form of worship in which a man and woman make a contract with the aim of achieving a sakinah life (calm, peaceful), mawaddah (loving and full of love and affection), and warahmah (life blessed by God). Marriage has a very important meaning and position in the order of human life. Because with marriage, a social relationship can be formed between two people of different sexes legally in a conjugal bond into one family. Furthermore, the family can continue to develop into community groups. The goal to be achieved from marriage is to achieve happiness in this world and the hereafter. The law of marriage can sometimes be a sunnah (mandub), sometimes it can be mandatory or sometimes it can be just change. Even under certain conditions it can be makruh. And there is also the law of marriage that is forbidden to do. Everything will depend on the condition and situation of a person and the problem. From a medical point of view, early marriage has a negative impact on both mother and child. According to sociologists, from a social perspective, early marriage can reduce family harmony. This is caused by unstable emotions, turbulence of youthful blood and immature way of thinking.